Familial aggregation of maxillary lateral incisor agenesis - Maciel, P. (2010)
In spite of recent developments, data regarding the genes responsible for the less severe forms of hypodontia are still scarce and controversial. This study addressed the hypothesis that agenesis of maxillary lateral incisors (MLIA) is a distinct type of hypodontia, by evaluating its familial aggregation and the occurrence of other types of ageneses or microdontia in probands' relatives. Sixty-two probands with MLIA were identified, and information was collected on 142 first-degree relatives. Relative risk (RR) was calculated and compared by re-assessment of data previously published for the Swedish, Utah, and Israeli populations, for the same trait. A RR of 15 was obtained in the Portuguese, 16 in the Swedish, 12 in Utah, and 5 in the Israeli population. Our results support a significant familial aggregation of MLIA, show that MLIA almost never segregates with other forms of agenesis, and suggest that microdontia of maxillary lateral incisors is part of the same phenotype.